1963
DOI: 10.1152/ajplegacy.1963.204.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Reflex antidiuresis after occlusion of common carotid arteries in hydrated dogs

Abstract: Common carotid arteries were occluded bilaterally for 5 min below the thyrocarotid arterial junctions in mildly hydrated, anesthetized dogs. Within 5–15 min after the occlusion, urine flow declined and remained below control values for 30–105 min. Concurrently, the urine became hypertonic to systemic plasma and there was no evidence for renal vasoconstriction or increased solute reabsorption. The decrement in urine flow was accounted for entirely by the decline in free-water clearance. Prolonged periods of occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1964
1964
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In fact, according to the atrial receptor hypothesis the lowered atrial pressure should be associated with a reduced urine flow. The reflex pathway, suggested by the data of Dieter - 8 and Okada et al,-° should increase renal nerve activity during stellate stimulation and thus decrease rather than increase urine flow. …”
Section: Discussionmentioning
confidence: 94%
“…In fact, according to the atrial receptor hypothesis the lowered atrial pressure should be associated with a reduced urine flow. The reflex pathway, suggested by the data of Dieter - 8 and Okada et al,-° should increase renal nerve activity during stellate stimulation and thus decrease rather than increase urine flow. …”
Section: Discussionmentioning
confidence: 94%
“…Secondly, Perlmutt (1963) found that the antidiuresis was seen only when carotid occlusion was applied below the thyrocarotid junction, but not when the occlusion was applied above the thyrocarotid junction. However, this latter manoeuvre would be expected to increase the general systemic blood pressure, as before, and there would also be an increased pressure at the thyrocarotid junction, which according to the theory of Share (1965) and Perlmutt (1963) would cause a diuresis.…”
mentioning
confidence: 83%
“…However, it is unlikely that the responses seen in . (Share, 1965) and antidiuresis is only observed when the occlusion is applied below the level of the thyrocarotid artery junction (Perlmutt, 1963). But these two studies reported conflicting results.…”
mentioning
confidence: 99%
“…Previous reports (1,2) indicate that reduced urine flow and free-water clearance resulted from occlusion of the carotid arteries below the junctions of the superior thyroid and common carotid arteries in hydrated dogs, whereas occlusion above innervated or below denervated junctions was ineffective. Since in all these instances the carotid sinus reflex was activated, the conclusion was drawn that the carotid sinus is not the receptor site involved in the initiation of the reflex antidiuresis.…”
mentioning
confidence: 87%
“…Mongrel carotid occlusion below the thyrocarotid junctions was the same as previously described (1). A femoral artery was cannulated for determining blood pressure with a Statham pressure transducer connected to a Grass ~o l ygraph, and an indwelling needle was placed in an external jugular vein for obtaining blood samples at 30-min intervals during subsequent clearance periods.…”
mentioning
confidence: 99%